Data driven stochastic modelling and simulation of cooling demand within breweries - Hubert, Stefan; Helmers, Thorben; Groß, Frauke; Delgado, Antonio (Journal of Food Engineering, 2016)
Over the last few decades the food and beverage industry has become increasingly aware of its energy and water usage. Customers are demanding an increasing level of sustainability. This is especially true within the brewery industry. The process of brewing itself is a demanding process, with respect to both energy and water requirements. To increase the knowledge about the holistic process chains, e.g. for decision making and for testing operational and procedural setups there is an evolving need for virtualisation. This paper focuses on modelling and simulation of parts within the process of brewing. The shown approach utilises reference nets as a flow-chart-like modelling environment. Models based on the Java programming language are implemented, dealing with stochastic and deterministic events. Results of eight different brew types are shown and a complete schedule with a total of 230 batches, portraying almost a year of production is being simulated.
UnivIS-Import:2015-10-26:Pub.2015.tech.ITC.stmmec.datadr
Keywords: Brewery; Energy demand; Reference nets; Simulation; Stochastic modelling; Uncertainty